Influence of acid hydrolysis reaction time on the isolation of cellulose nanowhiskers from oil palm empty fruit bunch microcrystalline cellulose - Razali, N. (North Carolina State University, 2017)
Cellulose nanowhiskers (CNW) were successfully isolated from oil palm empty fruit bunch microcrystalline cellulose (OPEFB-MCC) through sulfuric acid (H2SO4) hydrolysis with different reaction times. OPEFB-MCC was hydrolyzed with 64 wt.% H2SO4 at 40 °C and various reaction times (30, 60, and 90 min). Effects of the hydrolysis time on the morphologies and properties of the cellulose were evaluated by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), and transmission electron microscopy (TEM). The FTIR analysis showed that the chemical compositions of all of the samples were the same and represented the cellulose I structure. Hydrolysis time had little effect on the crystallinity index of the CNW, as was revealed by the XRD. The TEM images showed that the CNW produced with different reaction times had a rod-like shape and similar diameters and lengths. The produced CNW had better thermal stabilities than the OPEFB-MCC.